Evaluation of Information Technology Governance in Banking Companies Using BSC and COBIT 4.1 - Elvis Pawan (Institut Teknologi Bisnis AAS Indonesia, 2021)
Abstract - The era of industrial revolution 4.0, the progress of companies to achieve their vision and mission goals, is largely determined by the role of information technology, especially banking companies such as BPR PMM, the problem is that BPR PPM has not fully realized the importance of managing a business change, in order to maintain the company's existence. To determine the maturity level of the application of information technology in a company, it is necessary to conduct a thorough evaluation. In this study, there are seventeen processes in Cobit 4.1 that are solved on an internal balanced scorecard perspective. Cobit is a framework that is very well used in measuring the effectiveness of the application of information technology, while the balanced scorecard (BSC) is a framework that is very suitable to be applied to measure or assess the performance of a company. The combination of the two frameworks can provide a clear picture of internal perspectives that can be used by company leaders in improving information technology governance. This study resulted in a conclusion that the company maturity level in terms of business change management based on Cobit 4.1 and the internal balanced scorecard perspective has an average value of 2.90 at level 3 with defined categories.